Aplicación de la técnica didáctica el “Binomio fantástico” para mejorar la producción de textos (cuentos) en los alumnos del 4to grado de primaria en el área de comunicación en la I.E José Carlos Mariátegui - Fernández Saavedra, José Aníbal (2010)
The denominated investigation application of the didactic technique the Fantastic Binomial to improve the text production (stories) in the students of the fourth degree of primary education in the communication area in the educative lnstitution experimental "Jase Carlos Maria'tegui" of the province of La Rioja, _arose because it was observed that at the moment the educational ones do not use suitab/e techniques that allow to the development of the imagination and creativity of the students, and therefore that helps in the improvement in the text production (stories); they either do not use the suitable procedures that allow that the student manages to produce his own text (story) with coherence and cohesion. In this sense, the present investigation had like objective to apply to the didactic technique the "Fantastic Binomial", to improve the text production (stories) in the students of fourth degree of the primary level in the communication area, based on the theories of the significant learning, cultural and mental partner; also, on the basis of the studies that they precede to the present, the hypothesis assuming that with the systematization and application of the presented/displayed propasa! was formulated the story production will improve significantly. As far as the methodologic part, the investigation followed an pre experimental design with a sample of 15 students to those who test at the beginning of the investigation was administered to them pre and post test after applying eight sessions of learning on the basis of the propase didactic technique. With respect to the results, the contrast of the hypothesis was realized with a level of confidence of 99% by means of test t of student for the twin difference, accepting the investigation hypothesis, which means that the systematization application of the didactic technique the "Fantastic Binomial", has significantly improved the text production (stories) in the students of the fourth degree of primary education of the educative institution experimental "Jase Carlos Maria'tegui" of the province of La Rioja.